Lateral Reservoir Drainage in some Indonesia’s Sedimentary Basins and Its Implication to Hydrodynamic Trapping - Agus Mochamad Ramdhan; Lambok Maringan Hutasoit; Edy Slameto (Indonesian Journal on Geoscience, 2018)
DOI: 10.17014/ijog.5.1.65-80Lateral reservoir drainage is a hydrodynamic flow type driven by the difference in overpressure. It can lead to hydrodynamically tilted hydrocarbon water contact, and open an opportunity of finding oil and gas in places where previously are not considered as potential traps. In this paper, some examples of the presence of hydrodynamic traps in Indonesia’s sedimentary basin are discussed. Tilted hydrocarbon water contacts are present in some fields in the Lower Kutai Basin, and our interpretation is that regional lateral reservoir drainage is present in this basin and is responsible for the tilted contacts. It is also interpreted that lateral reservoir drainage leading to tilted hydrocarbon water contacts may be present at the Arun Field - North Sumatra Basin, Vorwata Field - Bintuni Basin, and BD Field - offshore East Java Basin. As most Indonesia’s sedimentary basins are overpressured, the presence of lateral reservoir drainage driven by overpressure difference in the same stratigraphic unit is very plausible to occur, opening the opportunity for hydrodynamically tilted hydrocarbon water contact to be present.